2014
DOI: 10.1186/bf03353208
|View full text |Cite
|
Sign up to set email alerts
|

The vorticity dynamics of instability and turbulence in a breaking internal gravity wave

Abstract: We perform a three-dimensional simulation of a breaking internal gravity wave in a stratified, compressible, and sheared fluid to investigate the vorticity dynamics accompanying the transition from laminar to turbulent flow. Baroclinic sources contribute preferentially to eddy vorticity generation during the initial convective instability of the wave field, yielding counter-rotating vortices aligned with the external shear flow. These vortices enhance the spanwise vorticity of the shear flow via stretching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…They simulated propagation of waves in a rectangle atmospheric region with horizontal and vertical dimensions of 120 and 48 km, respectively. Other authors (Fritts and Garten, 1996;Andreassen et al, 1998;Fritts et al, 1999) simulated the effect of atmospheric internal wave breaking due to Kelvin-Helmholtz instabilities. Their models are three-dimensional ones and wave propagation and breaking was simulated in rectangle regions with horizontal and vertical extensions of 4H Â 2H and 4H, respectively, where H is the scale height.…”
Section: Introductionmentioning
confidence: 99%
“…They simulated propagation of waves in a rectangle atmospheric region with horizontal and vertical dimensions of 120 and 48 km, respectively. Other authors (Fritts and Garten, 1996;Andreassen et al, 1998;Fritts et al, 1999) simulated the effect of atmospheric internal wave breaking due to Kelvin-Helmholtz instabilities. Their models are three-dimensional ones and wave propagation and breaking was simulated in rectangle regions with horizontal and vertical extensions of 4H Â 2H and 4H, respectively, where H is the scale height.…”
Section: Introductionmentioning
confidence: 99%
“…However, these PV anomalies could also result from vorticity dynamics involving baroclinic vorticity generation within the convectively unstable phase of the wave followed by vortex tilting and stretching (e.g. Fritts et al 1999), since these source terms in the absolute vorticity equation are implicitly contained in the advection term of the PV equation. Therefore, Fig.…”
Section: Qualitative Resultsmentioning
confidence: 98%
“…It was then shown that these convective overturning regions were associated with shedding streamwise counter vortices that eventually played a role in the large-scale dynamical influence of the simulated AP gravity wave (e.g. Fritts et al, 1999;Chen et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moet et al 16 showed that local changes in the vortex core radius are linked to instability and vortex bursting in subsonic flows. Fritts et al 17 pointed out the importance of interactions between vortical structures on compressible breakdown from a topological perspective. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%